Magnetic resonance spectroscopy in vivo of neurochemicals in a transgenic model of Alzheimer's disease: A longitudinal study of metabolites, relaxation time, and behavioral analysis in TASTPM and wild‐type mice. Issue 4 (3rd July 2012) - Forster, Duncan; Davies, Karen; Williams, Steve
<x xml:space="preserve">Abstract</x> Alzheimer's disease (AD) is the most common form of dementia in the elderly. Due to ongoing advances in our understanding of the underlying pathology of AD, many potential new targets for therapeutics are becoming available. Transgenic mouse models of AD have helped in furthering our understanding of AD and also provide a vehicle for preclinical testing of new, putative disease‐modifying therapeutics, which may have potential for translation to use in clinical trials. To identify possible translational biomarkers, we have studied the longitudinal cerebral metabolic pattern of the TASTPM transgenic AD mouse, a double transgenic mouse overexpressing human mutant amyloid precursor protein (hAPP695swe) and presenilin‐1 (M146V) by 1H magnetic resonance spectroscopy, along with concurrent brain T1/T2 mapping and behavioral testing. We found significant differences in creatine, glutamate, N‐acetylaspartate, choline‐containing compounds, and myo‐inositol between TASTPM and wild‐type mice. In the case of N‐acetylaspartate and myo‐inositol, there were similarities to differences detected in human AD. T1/T2 values were shorter overall in TASTPM mice, indicating possible differences in water content between TASTPM and wild‐type mice. In older TASTPM mice, exploratory behavior became more random, indicating a possible memory deficiency. The decrease in behavioral performance correlated in the transgenic group with higher expression of myo‐inositol. Magn Reson Med 69:944–955, 2013. © 2012 Wiley Periodicals, Inc.